The effect of ownership concentration on firm risk and value: evidence from Germany - Christoph Thalhammer (The Central European Review of Economics and Management (CEREM), 2023)
Aim: This paper aims to understand the effects of ownership concentration on firm risk and value. Design / Research methods: The author focuses on the largest publicly listed 91 German corporations in the time period 2010 to 2021. The resulting sample contains between 928 and 1051 observations and is analysed through a pooled OLS regression analysis. Ownership concentration is measured in terms of the number of blockholders, the size of the largest shareholder, and the Herfindahl Index of the ten largest shareholders. Firm value is captured with Tobin's Q and firm risk is computed as the annualised daily stock price volatility. Conclusions / Findings: It is found that ownership concentration affects firm risk significantly negatively. Moreover, results suggest an inverse U-shape relationship between ownership concentration and firm value. This relationship can be explained by combining the negative effects of rising ownership concentration on firm risk with its implications for the creation of firm value. Originality / Value of the article: The German market has used to have a network-like structure with a concentrated ownership structure. However, over the past two decades, it transformed towards a more Anglo-Saxon-like and market-based structure with a rather dispersed ownership structure. Furthermore, factors which govern the relationship between ownership concentration are used to explain parts of the relationship between firm value and ownership concentration in a new way, thereby adding value to understanding the latter, highly debated, relationship.
Keywords: G32; 330; Corporate Governance; Ownership Concentration; Blockholders; Firm Risk; Firm Value